Discriminative bag-of-visual phrase learning for landmark recognition - Chen, Tao (2013)
Bag-of-visual phrase (BoP) has been proposed and developed for landmark recognition recently. However, existing BoP methods for landmark recognition have two major shortcomings: (i) they try to construct a universal phrase vocabulary for all object categories, which lacks specific descriptive capabilities for a particular category, and (ii) they often adopt simple criterion such as the frequency information to mine the visual phrases, which may cause the selected phrases to be less discriminative or representative for recognition. In view of this, this paper proposes a new discriminative BoP approach for landmark recognition. First, the candidate visual phrases defined as adjacent pairwise words are selected for each category. A phrase-level similarity measure at the latent space is proposed to evaluate the semantic similarity between pairwise phrases. This is then integrated with the phrase frequency information to shortlist the discriminative phrases for each category through a proposed phrase ranking algorithm. Finally, the BoP and bag-of-words (BoW) histograms are combined through a pyramid matching method for recognition. Experimental results on two different datasets demonstrate that the proposed method is effective in landmark recognition.